Internet of Things: Key technology, architecture and challenging problems - Handong Zhang; Lin Zhu (2011 IEEE International Conference on Computer Science and Automation Engineering, 2011)
The development and application of the Internet of Things (IOT) and one of the key technologies "RFID technology" are introduced in detail to gain a better understanding of the IOT technology. For the working principle and mechanism of the IOT can be understood and grasped more easily, an architecture model of the IOT is established combined with the EPC global standards, and the working model of three layer consist of the sensing-layer, network-layer, and application-layer are given. To further promote the practical application of this IOT architecture model, some pressing issues are pointed out, and the smart nodes optimization problem, the information security issues and the data processing problem are emphasized, etc. The final conclusion provides some suggestions for the development of the IOT.